2017
DOI: 10.1016/j.ijhydene.2016.06.058
|View full text |Cite
|
Sign up to set email alerts
|

Risk and sustainability analysis of complex hydrogen infrastructures

Abstract: Building a network of hydrogen refuelling stations is essential to develop the hydrogen economy within transport. Additional, hydrogen is regarded a likely key component to store and convert back excess electrical power to secure future energy supply and to improve the quality of biomass-based fuels. Therefore, future hydrogen supply and distribution chains will have to address several objectives. Such a complexity is a challenge for risk assessment and risk management of these chains because of the increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Thomas and Griffin [40] name three stages of supply chains as the traditional stages: procurement (sourcing), production, and distribution. In more recent publications on the sustainability assessment of HSCs, however, we found that-even though the definitions were not homogeneous-the majority of publications defined the stages of the supply chain slightly different from the traditional three components, e.g., [37,[41][42][43]. For our manuscript, we followed the dominant definition in the literature and defined the relevant stages for our analysis as production, distribution, and use.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Thomas and Griffin [40] name three stages of supply chains as the traditional stages: procurement (sourcing), production, and distribution. In more recent publications on the sustainability assessment of HSCs, however, we found that-even though the definitions were not homogeneous-the majority of publications defined the stages of the supply chain slightly different from the traditional three components, e.g., [37,[41][42][43]. For our manuscript, we followed the dominant definition in the literature and defined the relevant stages for our analysis as production, distribution, and use.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Markert et al [27] and Kikukawa et al [28] study the risk assessment and analysis of hydrogen fuelling stations; Hansen [29], Kasai et al [30] and Kim et al [31] assess the safety risks of a hydrogen infrastructure; Moonis et al [32] discuss the commercial side of hydrogen as a fuel source; and Kim and Moon [33] publish on the strategic design of a hydrogen infrastructure. A major gap in the research on hydrogen as a fuel is a systematic evaluation method for determining risks in the development of a hydrogen infrastructure.…”
Section: Risk Assessment Techniquesmentioning
confidence: 99%
“…The social aspects of hydrogen usage have so far been addressed mainly either from a qualitative sustainable perspective or at a macroscopic scale to evaluate the social relevance of global scenarios. Firstly, several papers have been focused on hydrogen, as the main actor to make the change to a more sustainable scenario regarding mobility and production of energy ( Afgan et al, 2007 ;Chang et al, 2011 ;Hsu, 2013 ;Markert et al, 2016 ). Secondly, a few strategies have been assessed to narrow the gap towards a hydrogen economy ( Qadrdan et al, 2008 ;Moliner et al, 2016 ;Keles et al, 2008 ).…”
Section: Acronymsmentioning
confidence: 99%